2009
DOI: 10.22495/cocv7i1c3p1
|View full text |Cite
|
Sign up to set email alerts
|

Corporate governance and corporate performance: evidence from Kuwait

Abstract: An increasing number of recent corporate scandals and failures worldwide give rise to interest in the corporate governance structure in the performance of companies. This study investigates the relationship between corporate governance characteristics and performance of 66 non-financial companies listed on the Kuwait Stock Exchange (KSE) during the years 2004-2007. The findings of this study show that corporate governance characteristics such as board size, role duality, and less concentrated share ownership w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 54 publications
1
13
2
Order By: Relevance
“…In Kuwait, Al‐Shammari and Al‐Sultan (2009) investigated the relationship between corporate governance mechanisms and firm performance for non‐financial companies on the KSE from 2004 to 2007 and found a positive relationship between role duality and firm performance measures. In the Kuwaiti setting, listed firms are not required by law to separate the role of firm chairman and CEO (or managing director).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In Kuwait, Al‐Shammari and Al‐Sultan (2009) investigated the relationship between corporate governance mechanisms and firm performance for non‐financial companies on the KSE from 2004 to 2007 and found a positive relationship between role duality and firm performance measures. In the Kuwaiti setting, listed firms are not required by law to separate the role of firm chairman and CEO (or managing director).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Several studies in corporate governance literature have investigated the relationship between firm performance and board composition in Kuwait, including those of Al‐Shammari and Al‐Sultan (2009) and Al‐Saidi (2010). However, all of these studies excluded banks from their samples due to differences in the regulations and capital structures.…”
Section: Introductionmentioning
confidence: 99%
“…This finding was very close to the finding of Alfaraih et al 2012in their 2010 study of the ownership structure in Kuwait in which they found that the concentration of ownership by institutions was 55%. Also, Al-Shammari and Al-Sultan (2009) reported this concentration to be about 55%. Omran et al 2008) found that the concentration percentage of the largest shareholders averaged 48% for four Arab countries.…”
Section: Resultsmentioning
confidence: 91%
“…The mean value of board size is about 6.12, while board independence equals 82%, and family directors in Kuwait equals 23%. Al-Shammari and Al-Sultan (2009) found ownership concentration by large shareholders equals 55%, board independence equals 82%, and board size equals 6.39. Notes: ***, **, and * significant at the 0.01.…”
Section: Descriptive Analysismentioning
confidence: 98%